Stabilizing Planar Inverted Pendulum System Based on Fuzzy Nine-point Controller - Tang Yong-chuan; Liu Feng; Qi Qian; Yang Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In order to stabilize planar inverted pendulum, after analyzing the physical characteristics of the planar inverted pendulum system, a pendulum nine-point controller and a car nine-point controller for X-axis and Y-axis were designed respectively. Then a fuzzy coordinator was designed using the fuzzy control theory based on the priority of those two controllers, and the priority level of the pendulum is higher than the car. Thus, the control tasks of each controller in each axis were harmonized successfully. The designed control strategy did not depend on mathematical model of the system, it depended on the control experience of people or the control experts. The compared experiments showed that the control strategy was easy and effective, what was’s more, it had a very good robust feature. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.4146